Finite-time control for networked switched linear systems with an event-driven communication approach. Issue 2 (25th January 2017) - Wang, Shun; Zeng, Ming; Park, Ju H.; Zhang, Lixian; Hayat, Tasawar; Alsaedi, Ahmed
ABSTRACT: This paper is concerned with the network-based finite-time controller design problems for a class of switched linear systems with sampled-data control approach, the quantisation errors are also taken into account. A novel event-driven communication scheme is developed which can be seen as the extension of time-driven communication cases. By invoking an input-delay approach, the networked switched control systems are firstly modelled as a kind of switched time-delay systems with time-varying delays, upon which a set of mode-dependent controllers are then designed such that the reformulated switched system with time-varying delays is finite-time bounded and has a guaranteed noise attenuation performance in the finite-time H ∞ sense. Moreover, a co-design algorithm of mode-dependent control and event-driven communication is presented to find the optimal event-driven strategy for reducing transmission loads. Finally, a numerical example and an application to F-18 aircraft are provided to demonstrate the effectiveness and the advantages of the developed results.